Organic petrological and organic geochemical of tertiary coals within the west middle block of the Pinangah coal field, Sabah, Malaysia / Fatin Liyana Bt Alias - Alias, Fatin Liyana (2014)
The Tertiary Tanjong Formation coals exposed in the west middle block of the Pinangah Coalfield, central part of southern Sabah were analysed based on organic petrological and organic geochemical methods. The sediments of the Tanjong Formation were deposited in brackish water condition, based on limited biostratigraphic data (Collenette, 1965). The Tertiary Tanjong coals are humic and generally dominated by vitrinite, with significant amounts of liptinite and low amounts of inertinite macerals. Total organic carbon contents (TOC) of the coals range from 51.2 to 77.7 wt. %, and yield of bitumen values ranging from 57300 to 140000 ppm, which meet the standard as a source rock with excellent hydrocarbon-generative potential. Good liquid hydrocarbons generation potential can be expected from the Tanjong coals based on significant liptinitic content (> 15%). This is supported by their high hydrogen index up to 300 mg HC/g TOC, consistent with Type II and mixed Type II-III kerogen. The coal samples have vitrinite reflectance values in the range of 0.42%-0.66 Ro%, indicating immature to early mature stage for hydrocarbon generation. These vitrinite reflectance values also indicated that the Tanjong coals are within sub-bituminous B-A and high volatile bituminous C rank. Tmax values ranging from 419°C to 451°C are in good agreement with the vitrinite reflectance data. This is supported by biomarker maturity parameters as suggested by the C32 homohopane. The saturated fraction of the Tanjong coals are characterized by dominant odd carbon numbered n-alkanes (n-C23 to n-C33), high Pr/Ph ratios (8–18), high Tm/Ts ratios (6–28), and predominant of C29 regular sterane. Rhizophora, Cassuriana, Dactylocdalus and podocarpus are the types of pollen present in the analysed coal samples. Preservation Index versus Gelification Index facies diagram show coal samples fall within the depositional open marsh to fluvial environment on the lower delta plain field. This is supported by iv palynology result. All biomarker parameters and palynology result clearly indicate that the organic matter were derived from terrestrial inputs and deposited under marine influenced within suboxic condition on the lower delta plain.